Improving Students’ Ability in Writing Descriptive Text Using Example Non-Example Method at Eight Class of SMP Negeri 3 Ngimbang - Khoirul Huda; Dwi Purwanti (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2023)
The aim of this research is to know: (1) difference of descriptive writing skill between eighth class of SMP Negeri 3 Ngimbang who follow the learning of writing descriptive text using example non-example method with students who follow the learning of writing descriptive text without using example non-example method, (2) the effectiveness of the use of the example non-example method in learning to write descriptive text in the eighth grade of SMP Negeri 3 Ngimbang. This research is a quasi-experimental research using pretest-posttest control group design. The results of t-test calculations performed on the post-test scores between the control group and the experimental group showed that the t-count was 2.735 with db 48 and Sig. (2-tailed) 0.009. Sig value. (2-tailed) which is 0.009 is smaller than the significance level of 5% (0.009 <0.050). This shows that there is a significant difference of descriptive writing skill among eight grade students of SMP Negeri 3 Ngimbang who follow the learning of descriptive text writing using example non-example method with students who follow poetry writing lesson without using example non-example method. After the pre-test and post-test test of each group, it is seen that the difference of pre-test score and post-test score in the experimental group is larger than the control group (4.6> 2.52). This shows that the non-example example method is effectively used in writing descriptive text writing of eighth graders of SMP Negeri 3 Ngimbang.